THEORETICAL FOUNDATIONS OF FORECASTING ACTIVITIES AND THE NATURE OF MANAGEMENT OF ECONOMIC SYSTEMS - Alimov Fazliddin Xalimovich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
This article presents the theoretical foundations of forecasting activities and the essence of managing economic systems, the introduction of modeling into management, its application in economic calculations, and the most advanced methods of management and modern technical means of management.